2014
DOI: 10.1038/mp.2014.75
|View full text |Cite
|
Sign up to set email alerts
|

Dentate gyrus-CA3 glutamate release/NMDA transmission mediates behavioral despair and antidepressant-like responses to leptin

Abstract: Compelling evidence supports the important role of the glutamatergic system in the pathophysiology of major depression and also as a target for rapid-acting antidepressants. However, the functional role of glutamate release/transmission in behavioral processes related to depression and antidepressant efficacy remains to be elucidated. In this study, glutamate release and behavioral responses to tail suspension, a procedure commonly used for inducing behavioral despair, were simultaneously monitored in real tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 78 publications
2
54
0
Order By: Relevance
“…Our recent studies have shown that hippocampal Akt signaling is critical for the antidepressant-like effect of leptin in male mice (29). We therefore determined whether there is an estrous cycle stage-dependent difference in leptin-stimulated hippocampal Akt signaling.…”
Section: Effects Of Leptin On Hippocampal Akt Phosphorylation In Intamentioning
confidence: 95%
See 4 more Smart Citations
“…Our recent studies have shown that hippocampal Akt signaling is critical for the antidepressant-like effect of leptin in male mice (29). We therefore determined whether there is an estrous cycle stage-dependent difference in leptin-stimulated hippocampal Akt signaling.…”
Section: Effects Of Leptin On Hippocampal Akt Phosphorylation In Intamentioning
confidence: 95%
“…This dose of leptin was chosen because of its effectiveness in inducing antidepressant-like effects in intact male mice (19,23,29). The estrous cycle phase was identified based on vaginal lavage prior to the treatments.…”
Section: Experimental Design Experiments 1: Antidepressant-like Effectmentioning
confidence: 99%
See 3 more Smart Citations